Classification of the principles of design and technological development of an engineering product - Brailov Александр (Рroblems of engineering and professional education, 2023)
In the presented work, the main problem in the design of an engineering product is formulated. The basic principles of design and technological development of products are proposed and discussed. The classification of these principles is carried out. The classification is based on the ambiguity of the development process, its stage, intermediate results and the uniqueness of the specified characteristics and parameters of the product being developed.